1998
DOI: 10.1021/ma980032v
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Crystallization of the Planar Zigzag Form of Syndiotactic Polypropylene at 0 °C

Abstract: Introduction.Recently, syndiotactic polypropylene (sPP) with high stereoregularity was synthesized by Ewen et al. 1 Whereas early investigations carried out by using less syndiotactic samples had difficulties in precise characterization, the success of highly stereoregular polymerization made the detailed analysis of the crystal structure possible. A large number of investigations on the molecular chain conformation and molecular packing in crystals have also been reported for sPP. As for the polymorphs, four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
119
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(124 citation statements)
references
References 22 publications
5
119
0
Order By: Relevance
“…Highly syndiotactic poly(propylene) (sPP), recently synthesised with new metallocene homogeneous catalysts 1) , shows a very complex polymorphism [2][3][4][5][6][7][8][9][10][11][12] . A stable modification characterised by chains in the s(2/1)2 helical conformation can be packed in different crystalline cells (named Form I and II in ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly syndiotactic poly(propylene) (sPP), recently synthesised with new metallocene homogeneous catalysts 1) , shows a very complex polymorphism [2][3][4][5][6][7][8][9][10][11][12] . A stable modification characterised by chains in the s(2/1)2 helical conformation can be packed in different crystalline cells (named Form I and II in ref.…”
Section: Introductionmentioning
confidence: 99%
“…9) , depending on the degree of stereoregularity and thermal history of the samples. A different form (Form III) can be obtained by stretching the compression moulded samples or by crystallization at 0 8C 7,12) , and it is characterised by chains in zigzag planar conformation. Form IV was obtained by Chatani et al 8) by exposing fibre specimens in the zigzag conformation to organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…An efficiently quenched and rapidly analyzed sPP sample, sPP-h0, is completely amorphous, as seen by the appearance of its characteristic amorphous halo similar to that exhibited by an atactic poly(propylene) [35] (diffractogram represented at bottom of this figure). It is worth noting that preparation of amorphous sPP is not simple and the quenching at 0 8C induces formation of its mesomorphic form [36][37][38][39][40][41][42][43][44] for specimens with relatively high syndiotacticity. The moderately low syndiotactic degree exhibited by this sPP under study delays its crystallization rate and allows its preparation in a complete amorphous state, as seen for sPP-h0 diffractogram.…”
Section: Resultsmentioning
confidence: 99%
“…Form III can be obtained by stretching the most stereoregular sPP samples and, as occurs with Form IV, upon solvent treatments. Recently, the crystallization of the trans-planar Form III was reported for samples kept at 0 8C for a long time without any mechanical stress [24] though other authors have affirmed that the structure developed under those conditions do not correspond to the crystalline Form III but to a mesophase, or also paracrystalline, disordered phase. [23] When sPP, rapidly quenched from the melt in a cold bath, is brought to room temperature it is elastic due to a very low crystallinity, but the elastic behavior is soon lost due to a relatively rapid crystallization phenomenon and to the aging of the amorphous component.…”
Section: Introductionmentioning
confidence: 99%
“…[11 -13, 20] The trans-planar conformation of s-PP had been found [11, 20 -22] to be induced by cold drawing after quenching from the melt into an ice/water mixture. More recently, Nakaoki et al [12,23,24] reported that the crystallization of the trans-planar form is induced spontaneously at 0 8C in a period of about 20 h without any mechanical stress. In our studies, the formation of the trans-planar conformation may be explained by the interactions between polymer chain and solvent molecules.…”
Section: Resultsmentioning
confidence: 99%